Special Slums: Chengzhongcuns in China - Zhou, Nan (Social Thought and Research, 2025)
This paper explores the emergence and socio-economic dynamics of chengzhongcuns (城中村, “urban villages”) as a manifestation of social disorder within China’s rapid urbanization, driven by neoliberal reforms. It examines how chengzhongcuns developed as rural areas engulfed by expanding cities; the hukou (户口, “household registration”) system and land ownership policies from the Mao era continue to shape these spaces. Chengzhongcuns are not fully integrated into formal urban planning due to the unique land ownership system, where rural land remains collectively owned by villagers, unlike urban land, which is state-owned. This paper highlights the key differences between chengzhongcuns and slums in other developing countries, particularly how chengzhongcuns are legally distinct and intentionally maintained within the current land and governance framework rather than being a product of government failure. The socio-economic challenges faced by migrant workers in these spaces, especially the rise of the Sanhe dashen (三和大神, “Sanhe gurus”) subculture, further illustrate the marginalization and inequality within China’s urban economy. By situating chengzhongcuns in both local and global contexts of informal urbanization, this paper offers insights into China’s unique approach to urban development, emphasizing how the persistence of chengzhongcuns reflects broader patterns of social inequality in rapidly urbanizing countries.